The Relationship between Insurance Participants' Knowledge of Pending Claims: A Study on Insurance Managed by PT. Multiniaga Intermedia Proteksi - Tantri Wilananda; Daniel Happy Putra; Puteri Fannya; Lily Widjaja (Archives of The Medicine and Case Reports, 2023)
The impact of pending claims can affect insurance service activities, becoming hampered and officers' workloads increasing because they have to revise pending claims that are sent. This study aimed to assess the relationship between insurance participants' knowledge of the occurrence of pending claims: a study on insurance managed by PT. Multiniaga Intermedia Proteksi. This study was an observational study of cross-sectional design. A total of 107 research subjects participated in this study. The results of this study show that the claim submission process at PT. Multiniaga Intermedia Proteksi had 107 claims submitted to insurance, and it was known that the results of paid claims submissions were 87 submissions (81.3%), and pending submissions were 20 submissions (18.7%). The results of participants' level of knowledge regarding submitting claims were obtained from 107 respondents. The average value of participants' knowledge was 89.15, with a median of 86.67. The highest value was 86.67. The lowest score obtained by respondents was 60, and the highest score was 100 as the results of knowledge testing on the results of claim status using the t-test, obtained with a probability value (Sig.) 0.196 > 0.1, indicating that knowledge has no significant effect on submitting claims.